PERANCANGAN ULANG UI/UX WEBSITE BUMDES BATURITI MENGGUNAKAN METODE SUS DAN DESIGN THINKING - Ida Bagus Indra Dewangkara; Made Niken Novianti; Putu Agisna Fransisco Sara; Ni Putu Ana Rainita (PROGRESS, 2023)
Badan Usaha Milik Desa (BUMDes) Baturiti is one of the businesses managed by the Baturiti village government. In this technological era, BUMDes Baturiti has a website used for marketing their products. Surprisingly, the BUMDes Baturiti website has a user interface and user experience (UI/UX) that falls into the "Poor" category. This was revealed after conducting UI/UX testing using the System Usability Scale (SUS) method. SUS is a method for evaluating the usability of a product or system based on user perceptions. This method uses a questionnaire consisting of 10 items to evaluate the user's experience in using a product or system. The average score obtained from the first testing was 33.16, falling into the "Poor" category. Subsequently, this research focused on redesigning the UI/UX using the design thinking Smethod, a method for generating solution ideas for a problem. This research was carried out by implementing all stages of design thinking, namely empathize, define, ideate, prototype, and testing. After redesigning the prototype and conducting a second round of testing, the BUMDes Baturiti website prototype obtained a score of 88.5, falling into the "Highly Acceptable" category. Thus, the redesigned UI/UX prototype for BUMDes Baturiti is highly suitable for further development in the future.